Pathogenesis of chronic Chagas' myocarditis - Rossi, Marcos A. (1995)
The pathogenesis of chronic Chagas' myocarditis is still not completely understood. Several theories have been advanced: 1)direct tissue destruction by Trypanosoma cruzi; 2) neurogenic theory; 3) anti-heart immune reactions; and 4) microvascular disease. We present herein a dynamic alternative hypothesis. We believe that the development of myocarditis is related to progressive and additive focal cellular necrosis, and associated reactive and reparative myocardial fibrosis and surrounding myocyte hypertrophy. These processes may be initiated and perpetuated by anti immune factors and alterations in the myocardial microcirculation. The destruction of the ganglion cells of the heart may be involved in the patho-clinical evolution of chronic Chagas' cardiopathy. This could imply future therapeutic strategies in the management of chronic Chagas' patients to enhance medical treatment and, hopefully, improve prognosis.